Profiling hormonal contraceptive use and perceived impact on training and performance in a global sample of women rugby players - Brown, N.; Roldan-Reoyo, O.; Williams, G. K. R.; Stodter, A.; Moore, I. S.; Mackintosh, K. A.; McNarry, M. A.; Williams, E. M. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The potential impact of hormonal contraceptives (HCs) on player health and performance in women`s rugby union (rugby) is not well understood, despite rugby`s growing popularity worldwide. This study investigated the prevalence of HC use and reported associations with training and performance in a global sample of women rugby players.